Challenges and Opportunities in Teaching Marxist Theory Courses: A Quality Assessment Study under Plithogenic Sets - Qingchao Wang (Neutrosophic Sets and Systems)
Teaching Marxist Theory in higher education institutions presents both challenges and opportunities in the modern academic landscape. As societies evolve, so do pedagogical methods, student expectations, and ideological perspectives, creating a dynamic environment for delivering and assessing Marxist education. This study explores the complexities of teaching Marxist Theory, focusing on curriculum relevance, student engagement, instructional methodologies, and the integration of contemporary socio-political contexts. By employing a quality assessment approach, we analyze the effectiveness of teaching strategies and the factors that influence students' comprehension and critical thinking. Additionally, we highlight the impact of technological advancements and interdisciplinary integration on improving educational outcomes. We use the Plithogenic Set to deal with uncertainty information in the decision making. We use two methods, such as LMAW to obtain the criteria weights and the MOORA method to obtain the ranks of the alternatives. We show the comparative analysis between proposed approach and other methods. The results show the proposed method is strong and effective compared to other methods.